Reflecting the System and Approach to Islamic Education Financing in Indonesia - Aufatus Syakira Mardhatillah; Muhammad Hafis Bin Redwan; Hamdi Abdul Karim (ALSYS, 2026)
Educational financing is a crucial component in the implementation of Islamic education because it supports institutional operations, improves learning quality, and enables the development of educational facilities and infrastructure. This study aims to analyze the system and approach of Islamic educational financing and its implementation in improving the quality of Islamic educational institutions. Using a qualitative approach with library research, data were obtained from scientific sources, including journals, books, and academic documents relevant to the research theme. Data were collected through documentation and literature review and analyzed using content analysis. The findings indicate that Islamic educational financing is sourced from the government, community, parents, social institutions, productive enterprises, and Islamic philanthropic instruments, including zakat, infaq, sedekah, and waqaf (ZISWAF). The financing approach emphasizes efficiency and effectiveness, participation, entrepreneurship, transparency, accountability, and Islamic values. The implementation of a robust financing system has been shown to improve the quality of management in Islamic educational institutions and strengthen institutional sustainability. This study contributes to the development of Islamic education management, particularly in promoting innovative, transparent, and sustainable educational financing systems.